Mycosis fungoides, classic hypopigmented variety in a 6-year-old boy. - Pastura, M.I.; Massimo, I.C.; Loperfido, F.; Vitulli, L.; Massimo, J.A. (European Journal of Pediatric Dermatology, 2023)
In children, mycosis fungoides is the most frequent primary cutaneous T-cell lymphoma and the hypopigmented variant is the most frequent presenting form at this age. Its similarity to other inflammatory skin disorders, such as pityriasis alba, vitiligo, atopic dermatitis or pityriasis versicolor delays the diagnosis, which is reached 2-7 years after the onset of the first symptoms. Histology and immunohistochemistry are essential for a correct diagnosis. The case of a 6-year-old boy with hypopigmented variant of mycosis fungoides was described and the diagnostic criteria and therapeutic options were reviewed.